Lack of multidisciplinary collaboration is a barrier to outcomes research - GARDNER, JOANNE K.; RALL, LAURA C.; PETERSON, CATHERINE A. (Journal of the American Dietetic Association, 2002)
Objectives To identify and describe methods of collaboration used by dietitians to conduct outcomes research and to identify perceived barriers to participation in outcomes research. Design A questionnaire was mailed to dietitians to obtain descriptive information about outcomes research involvement. Details of collaborative research experiences were collected in follow-up telephone interviews. Subjects Subjects were a regional sample of 300 dietitians from the Clinical Nutrition Managers practice group of The American Dietetic Association. One hundred fifty-three subjects (51%) responded to the questionnaire and 25 of 42 eligible respondents were interviewed. Analysis Frequency counts on questionnaire and closed-ended interview data were analyzed. χ 2 tests were used to identify significant associations between participation in outcomes research and demographic variables. Content analysis of open-ended interview data was used to detect emergence of recurrent themes. Results Forty-two (27%) respondents had conducted outcomes research. Although all respondents collaborated on at least 1 project, half collaborated only with other dietitians, and 27 of 42 (64%) did not report research findings outside their facility. Interview data suggest that collaboration, especially between disciplines, enhances the entire research process and generates benefits beyond the specific project. The most frequently cited barriers among respondents who had not conducted outcomes research (n=111) were lack of research skills (65%) and lack of time or staff (41%). Applications These findings support the assertion that lack of multidisciplinary involvement is a barrier to generating evidence of nutrition therapy effectiveness. Educators, health care professionals, and dietitians must model and encourage multidisciplinary, collaborative outcomes research in diverse practice settings. J Am Diet Assoc. 2002;102:65-71.